Ovarian pathology of puberty and adolescence. - Archard, Arturo (2015)
It must be stated at the outset that when we talk of ovarian pathology of puberty and adolescence understand that the dominant factor pathological disorder resides in the ovary. However, we can not admit but isolated cases limited gonadal pathology, as with varying intensity these disorders are directly or indirectly influenced by the action of the hypothalamus-pituitary complex acting on the ovary by double hormonal and nervous mechanisms.